Sustainable Urban Development in Jakarta: Pentahenix and Public Perception Analysis - Ahmad Ghazy Dananjaya (Program Studi Manajemen Sekolah Pascasarjana Universitas Simalungun, 2025)
This study examines the complexities of urban planning and development in DKI Jakarta, a megapolitan facing infrastructural pressures and environmental challenges due to rapid urbanization. Employing a mixed-methods approach, this study analyzes development effectiveness by integrating the perspectives of Pentahelix model stakeholders through qualitative interviews with the quantitative perceptions of 400 public respondents. The quantitative results indicate that public satisfaction is significantly driven by pragmatic and directly experienced variables: Technology Innovation (β=0.348), which offers daily efficiency, and Public Participation (β=0.275), which fosters a sense of ownership. Conversely, fundamental variables such as Environmental Sustainability and Spatial Policy Effectiveness were not statistically strong predictors of general satisfaction, indicating a disconnect between expert priorities and public perception. The qualitative findings clarify this disconnect, highlighting a sharp gap between high-level policy design and on-the-ground implementation realities, as well as conflicting priorities among stakeholders. This research concludes the existence of a 'development paradox,' where short-term, pragmatic benefits more decisively shape public perception than long-term sustainability goals. To build a resilient city, the government must balance macro-strategic plans with tangible, inclusive wins that are directly felt by its citizens, transforming long-term objectives into currently relevant achievements